2021
DOI: 10.1142/s1793292021501277
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Electrochemical Detection of Ascorbic Acid, Dopamine and Uric Acid Using the Composite Materials of Fe3O4 and Nitrogen Self-Doped Sunflower Plate-Derived Carbon

Abstract: A simple pyrolysis, activation and hydrothermal method was utilized to synthesize composite materials (Fe3O4/SFP) of ferroferric oxide and nitrogen self-doped sunflower plate-derived carbon for the simultaneous electrochemical sensing of ascorbic acid (AA), dopamine (DA) and uric acid (UA). The Fe3O4/SFP had synergistic catalytic effect on target molecules, and the oxidation peak potential of AA, DA and UA was well distinguished in the differential pulse voltammetry determination. Under the optimal conditions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…To study this effect, the pH of the solution was adjusted from 6 to 9; lower pHs favor partial dissolution of magnetite in the medium [25]. Figure 8 shows that there is not a great variation in the detection signal with pH, but it can be observed that the current gradually decreases with increasing or decreasing pH; similar results have been obtained using Fe 3 O 4 and nitrogen self-doped sunflower plate-derived carbon as an electrochemical sensor [26]. The best pH seems to be approximately 7.5 for uric and ascorbic acid and 7 for DA.…”
Section: Resultssupporting
confidence: 56%
“…To study this effect, the pH of the solution was adjusted from 6 to 9; lower pHs favor partial dissolution of magnetite in the medium [25]. Figure 8 shows that there is not a great variation in the detection signal with pH, but it can be observed that the current gradually decreases with increasing or decreasing pH; similar results have been obtained using Fe 3 O 4 and nitrogen self-doped sunflower plate-derived carbon as an electrochemical sensor [26]. The best pH seems to be approximately 7.5 for uric and ascorbic acid and 7 for DA.…”
Section: Resultssupporting
confidence: 56%